Временные предпочтения: отбор или социализация (исследование украинских студентов) - Клочко, М.; Ордешук, П. (Социология: теория, методы, маркетинг, 2005)
Most economic theories assume that the discount people they apply to the future – the weight given to the future relative to the present in their decision making — is fixed, exogenously determined, and essentially the same across a society. Relevance of this assumption derives from the fact that this parameter of an individual’s choice is critical in determining the likelihood of a person’s engagement in cooperative action, as well as the likelihood that they will abide by democratic principles and participate constructively in the development of efficient and cooperative markets. Using a sample of Ukrainian youth — those who have emigrated to the West to complete their studies as compared to those who remain in Ukraine — we question the validity of this assumption. We suggest that not only are those students who travel to the West different from Ukraine’s student population generally in terms of the time discounting they apply to the future, but also that this discount changes as a function of one’s length of stay in the West so as to make them more amenable to cooperative action.